Diagnosis of abdominal angiostrongyliasis by PCR from sera of patients - Silva Ana Cristina Arámburu da; Graeff-Teixeira Carlos; Zaha Arnaldo (Revista do Instituto de Medicina Tropical de São Paulo, 2003)
Abdominal angiostrongyliasis is a zoonotic infection caused by an intra-vascular nematode parasitic of wild rodents, Angiostrongylus costaricensis. No parasitological diagnosis is currently available and immunodiagnosis presents several drawbacks. Primers constructed based on a congeneric species, A. cantonensis, were able to amplify a 232 bp fragment from serum samples of 3 patients with histopathological diagnosis. Extraction was better performed with DNAzol and the specificity of the primers was confirmed by Southern blot. This disease has been diagnosed with frequency in south of Brazil, thus, this method appears like the important and unpublished alternative to improve diagnostic of disease.